Functional Analysis of MaWRKY24 in Transcriptional Activation of Autophagy-Related Gene 8f/g and Plant Disease Susceptibility to Soil-Borne Fusarium oxysporum f. sp. cubense - Liu, Guoyin (Pathogens, 2019)
WRKYs play important roles in plant development and stress responses. Although MaWRKYs have been comprehensively identified in the banana (Musa acuminata), their in vivo roles and direct targets remain elusive. In this study, a transcript profile analysis indicated the common regulation of MaWRKYs transcripts in response to fungal pathogen Fusarium oxysporum f. sp. cubense (Foc). Among these MaWRKYs, MaWRKY24 was chosen for further analysis due to its higher expression in response to Foc. The specific nucleus subcellular location and transcription activated activity on W-box indicated that MaWRKY24 was a transcription factor. The correlation analysis of gene expression indicated that MaWRKYs were closely related to autophagy-associated genes (MaATG8s). Further analysis showed that MaWRKY24 directly regulated the transcriptional level of MaATG8f/g through binding to W-box in their promoters, as evidenced by quantitative real-time Polymerase Chain Reaction (PCR), dual luciferase assay, and electrophoretic mobility shift assay. In addition, overexpression of MaWRKY24 and MaATG8f/g resulted in disease susceptibility to Foc, which might be related to the activation of autophagic activity. This study highlights the positive regulation of MaWRKY24 in transcriptional activation of autophagy-related gene 8f/g in the banana and their common roles in disease susceptibility to soil-borne Foc, indicating the effects of MaWRKY24 on autophagy and disease susceptibility.